2019
DOI: 10.5194/hess-23-549-2019
|View full text |Cite
|
Sign up to set email alerts
|

Emergent stationarity in Yellow River sediment transport and the underlying shift of dominance: from streamflow to vegetation

Abstract: Abstract. Soil erosion and sediment transport play important roles in terrestrial landscape evolution and biogeochemical cycles of nutrients and contaminants. Although discharge is considered to be a controlling factor in sediment transport, its correlation with sediment concentration varies across the Yellow River basin (YRB) and is not fully understood. This paper provides analysis from gauges across the YRB covering a range of climates, topographic characteristics, and degrees of human intervention. Our res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The nonlinear effect of vegetation in terms of sediment resistance to erosion follows that of the previous literature [51,52]. Vegetation is undeniably an important determinant of sediment reduction and could be considered as a useful indicator of both soil erosion and the transport of sediment in the QRB, despite the fact that the possible contribution of additional factors is not accounted for here.…”
Section: Relationship Between Precipitation Vegetation and Erosionsupporting
confidence: 65%
See 2 more Smart Citations
“…The nonlinear effect of vegetation in terms of sediment resistance to erosion follows that of the previous literature [51,52]. Vegetation is undeniably an important determinant of sediment reduction and could be considered as a useful indicator of both soil erosion and the transport of sediment in the QRB, despite the fact that the possible contribution of additional factors is not accounted for here.…”
Section: Relationship Between Precipitation Vegetation and Erosionsupporting
confidence: 65%
“…These conditions contrast with the QRB, with an arid and semi-arid climate and relatively poor vegetation coverage. Despite this difference, a similar bell-shaped relationship was also discovered among precipitation, vegetation, and sediment yield in the QRB, the LP [51], and the YR [52]. This suggests that the bell relationship among these variables does not only occur in humid and well-vegetated regions but can also be applicable in arid and poorly-vegetated areas.…”
Section: Response Of Sediment To the Coupling Effect Of Vegetation An...mentioning
confidence: 67%
See 1 more Smart Citation
“…Reservoirs play a vital role in the sediment movement in rivers [46,61,62], and larger reservoirs may have a more substantial effect on the transport processes than smaller ones. Many studies have found a connection between vegetation indices such as NDVI and EVI and catchment sediment discharge [63,64]. We found that the importance of NDVI and EVI was generally higher than that of specific land cover types.…”
Section: Rock Chemistry Vegetation Indices and Precipitation Affect M...mentioning
confidence: 50%
“…Given the thick loess layers, deep groundwater table, and short‐duration heavy rainfall events, infiltration‐excess overland flow was considered as the dominant runoff generation mechanism in the Loess Plateau (Liu et al, 2012). With the recovery of vegetation in the Loess Plateau, studies showed that the runoff coefficient decreased with the elevation of vegetation coverage (Liu et al, 2014; Qiu et al, 2017; Ye et al, 2019). It has been proved that large‐scale ecological restoration accounted a relatively significant proportion for the streamflow reduction (Liang et al, 2015; Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%